Childhood colic management under the optics of mothers and of the family health team - Flávia Corrêa Porto de Abreu-D'Agostini; Julia Baldi Vieira; Beatriz Castanheira Facio; Lislaine Aparecida Fracolli; Márcia Regina Cangiani Fabbro; Elenice Valentim Carmona; Monika Wernet (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to unveil the interrelation of childhood colic management by mothers and Family Health Strategy professional. Methods: a qualitative, exploratory and descriptive research carried out with 4 Family Health Strategy teams and 31 mothers who experienced childhood colic. Data collection included, respectively, focus group and individual unstructured interview. Symbolic Interactionism was adopted as the theoretical framework, and Narrative Research as methodological. Results: two themes emerged: "Colic approach" and "Social support and care". Professional childhood colic management is based on diagnosis and drug interventions. For mothers, the child's suffering and impotence in the face of the disease stand out. Final considerations: childhood colic is socially widespread because it is a physiological and self-limiting event. Mothers felt helpless in the face of childhood colic. Professionals felt the need to expand their care, with a view to achieving maternal suffering and alleviating it.